Mutatis mutandis: Are we diagnosing too many people with non-celiac gluten sensitivity? Multiple case report - Borghini, Raffaele; Donato, Giuseppe; Tola, Marco Di; Isonne, Claudia; Picarelli, Antonio (Turkish Journal of Gastroenterology, 2014)
Abstract We report three patients presenting with gluten-related signs and symptoms. Since villous height/crypt depth ratio, intraepithelial lymphocyte count, and serum antibody tests were not diagnostic for celiac disease (CD), a diagnosis of non-celiac gluten sensitivity (NCGS) was suggested. On the other hand, antibodies suggestive for CD surprisingly showed positive results in the duodenal biopsy organ culture of all three cases. The reported cases suggest the precious potential role that organ culture systems may play in differentiating CD from NCGS. This method should be recommended when gluten-related disorders are suspected in order to reduce the inappropriate diagnosis of NCGS.